Productivity and economic planning : exchanges of experience organised by the Development Centre in liaison with productivity bodies in OECD member countries and in developing countries - Organisation for Economic Co-operation and Development (Paris : Development Centre, Organisation for Economic Co-operation and Development, 1970)
The aim of this publication is to be attained if those in charge of planning and productivity policies can find in it some relevant material to help them solve one of the problems which, rightly, are at the centre of their efforts to develop a higher degree of efficiency
sju 23/01/2019
Loans
Keywords: Economic development; Industrial productivity centers